Mixed and mixing layer depths in the ocean surface boundary layer under conditions of diurnal stratification. Issue 23 (4th December 2014) - Sutherland, G.; Reverdin, G.; Marié, L.; Ward, B.
Abstract: A comparison between mixed (MLD) and mixing (XLD) layer depths is presented from the SubTRopical Atlantic Surface Salinity Experiment (STRASSE) cruise in the subtropical Atlantic. This study consists of 400 microstructure profiles during fairly calm and moderate conditions (2 < U 10 < 10 m s −1 ) and strong solar heating O(1000 W m −2 ). The XLD is determined from a decrease in the turbulent dissipation rate to an assumed background level. Two different thresholds for the background dissipation level are tested, 10 −8 and 10 −9 m 2 s −3, and these are compared with the MLD as calculated using a density threshold. The larger background threshold agrees with the MLD during restratification but only extends to half the MLD during nighttime convection, while the lesser threshold agrees well during convection but is deeper by a factor of 2 during restratification. Observations suggest the use of a larger density threshold to determine the MLD in a buoyancy driven regime. Key Points: We obtained density and dissipation measurements at the ocean surface We made estimates of the mixed (MLD) and mixing (XLD) layer depths We found a relationship between MLD and XLD for buoyancy‐driven conditions